Evaluating the efficacy of smartwatch-based mobility reminders in pressure sore prevention: a pilot observational study - Aggarwal, Ankit; Tiwari, Raja; Dash, Suvashis (International Surgery Journal, 2025)
Wearable technology has gained prominence in healthcare for its ability to enhance patient care, especially for individuals with mobility limitations who are at risk for pressure sores. This pilot study aimed to evaluate the effectiveness of wearable smartwatches in providing mobility reminders to seven patients-three wheelchair-bound and four bedridden-to support regular movement and prevent the development of pressure sores. The study explored the ability of wearable device to deliver real-time notifications for position changes and movement, empowering patients to become more proactive and independent in managing their mobility-related needs. Patients reported enhanced autonomy in maintaining movement routines, with noticeable benefits in pressure sore prevention and a reduced dependency on caregivers. However, the study also identified limitations, such as occasional false-positive alerts, which created minor disruptions, particularly during periods of minimal activity like sleep. Calibration of the devices mitigated some of these challenges, improving the user experience for most patients. Overall, wearable technology showed promise in improving care quality and patient outcomes, with further refinement and personalization required for broader clinical use.